Changes in the role of the political parties and institutions in the post-democracy - Dimitrov, Dimitar V. (Sociološki pregled, 2021)
The article discusses the changes in the role of the political parties and institutions in the modern post-democratic societies. The goal of this paper is to present and analyze the models of establishing and functioning of the political parties and institutions in the post-democratic era, their relation with the contemporary political realities in Bulgaria and in the countries of the European Community. The main approach in the study and the analysis of the problems posed to the political parties is sociological, combined with the interdisciplinary one. The models of the political parties and institutions are traced and analyzed through the eyes of the modern political science. Outlined is the fact that there is a real danger political parties to become dependent on corporate elites and the widespread political populism. Real conditions and approaches for overcoming these shortcomings are indicated.